2012
DOI: 10.1002/mrd.22042
|View full text |Cite
|
Sign up to set email alerts
|

The importance of mitochondrial metabolic activity and mitochondrial DNA replication during oocyte maturation in vitro on oocyte quality and subsequent embryo developmental competence

Abstract: Mitochondrial metabolic capacity and DNA replication have both been shown to affect oocyte quality, but it is unclear which one is more critical. In this study, immature oocytes were treated with FCCP or ddC to independently inhibit the respective mitochondrial metabolic capacity or DNA replication of oocytes during in vitro maturation. To differentiate their roles, we evaluated various parameters related to oocyte maturation (germinal vesicle break down and nuclear maturation), quality (spindle formation, chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 45 publications
(66 reference statements)
3
90
1
2
Order By: Relevance
“…It has been proposed that development is affected by lower numbers of mitochondria or at least of copies of mtDNA (Ge et al 2012). However, vitamin K 2 was shown not to have any impact on the mtDNA/nDNA ratio (Rao et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that development is affected by lower numbers of mitochondria or at least of copies of mtDNA (Ge et al 2012). However, vitamin K 2 was shown not to have any impact on the mtDNA/nDNA ratio (Rao et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, centrifugation followed by the removal of the enriched mitochondrial fraction did not affect the developmental competence of embryos [8]. Conversely, reducing the mtDNA number using DCC during IVM resulted in a low development ratio of blastocysts [27]. In experiment 1, the mtDNA number in noncleaved oocytes was the lowest in the 2- to 3-cell, 4- to 7-cell, and >7-cell stage embryos, although the mtDNA number did not differ among the 3 stages.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that mitochondrial damage caused by CCCP treatment is eliminated by the proteasome and that these mitochondria are replaced by de novo-synthesised mitochondria during oocyte maturation. Ge et al (2012) reported that FCCP treatment of oocytes decreases maturation ability and spindle stability but does not alter the Mt number. We speculate that the reported result may be due to the presence of both pathways of mitochondrial biogenesis and degradation.…”
Section: Mitochondrial Impairments and Kineticsmentioning
confidence: 99%